Additions, corrections and comments to the Red List of bryophytes from mainland Spain and the Balearic Islands - Sáez, Llorenç; Ruiz, Elena; Brugués, Montserrat (Mediterranean Botany, 2018)
This article is a review of the conservation status of several taxa of bryophytes that were included in the Red List of Mainland Spain and the Balearic Islands, and those that were omitted, but should have been featured on the basis of most recent data. Of the 33 studied species that were regarded as threatened in the Red List, 31 have been downlisted upon re-evaluation, mostly as a result of better knowledge of species and their distribution. On the other hand, this study highlights the most urgent need to review all taxa assigned to the “Deficient Data” category in the Red List since most of these taxa are precisely the most likely to be truly threatened.